Magnetic resonance imaging of 1H long lived states derived from parahydrogen induced polarization in a clinical system - Graafen, Dirk (2016)
Hyperpolarization is a powerful tool to overcome the low sensitivity of nuclear magnetic resonance (NMR). However, applications are limited due to the short lifetime of this non equilibrium spin state caused by relaxation processes. This issue can be addressed by storing hyperpolarization in slowly decaying singlet spin states which was so far mostly demonstrated for non-proton spin pairs, e.g. 13C-13C. Protons hyperpolarized by parahydrogen induced polarization (PHIP) in symmetrical molecules, are very well suited for this strategy because they naturally exhibit a long-lived singlet state. The conversion of the NMR silent singlet spin state to observable magnetization can be achieved by making use of singlet-triplet level anticrossings. In this study, a low-power radiofrequency pulse sequence is used for this purpose, which allows multiple successive singlet-triplet conversions. The generated magnetization is used to record proton images in a clinical magnetic resonance imaging (MRI) system, after 3 min waiting time. Our results may open unprecedented opportunities to use the standard MRI nucleus 1H for e.g. metabolic imaging in the future.